(In)equality and the South African Constitution. Issue 6 (2nd November 2019) - Albertyn, Catherine
ABSTRACT: Does the South African Constitution constrain or empower government, courts and citizens in addressing systemic social and economic inequalities? This article argues that the Constitution is explicitly 'transformative', but is an enabling document, providing 'scaffolding' for political and legal activities. It is government, strong institutions and civil society that are ultimately responsible for securing its equality aspirations. Here the Constitution admits of different understandings of equality and different economic and social policy choices. This article identifies these contested meanings of equality and suggests that a liberal egalitarian/social democratic version is dominant in policy choices and the jurisprudence of the Constitutional Court. It illustrates this with reference to the Court's jurisprudence on equality, and suggests that more radical and transformative interpretations remain possible. However, it concludes that we cannot escape politics, the need for good policy choices and effective implementation and enforcement.